Nudges to reason: not guilty - Levy, Neil (Journal of medical ethics, 2018)
I am to grateful to Geoff Keeling for his perceptive response1 to my paper.2 In this brief reply, I will argue that he does not succeed in his goal of showing that nudges to reason do not respect autonomy. At most, he establishes only that such nudges may threaten autonomy when used in certain ways and in certain circumstances. As I will show, this is not a conclusion that should give us grounds for particular concerns about nudges.Before turning to this issue, let me correct some small issues of interpretation of my paper. Keeling takes me to be committed to three descriptive claims: (1) that we have entered a post-truth era, (2) that our problem with the rational assessment of evidence is explained by or stems from the backfire effect and (3) that nudges to reason work by exploiting affective mechanisms. I am not committed to accepting any of these claims. …